Performance of multi-soil-layering (MSL) urban domestic wastewater treatment system - Haribowo, Riyanto; Prayogo, T.B.; Shaleha, N.N.; Hafni, K.N. (Civil and Environmental Science Journal (CIVENSE), 2020)
This research has the objective of examining the efficiency optimization of a multisoil-layering (MSL) system in three stages through the selection of the most efficient material for permeable layers. The utilized charcoal variations were coconut shell charcoal, rice husk charcoal, and corncob charcoal. The utilized incoming discharge for Q1 and Q2 were 0.0063 L/second and 0.0126 L/second. In the first stage of processing, the pumice and zeolite in Q1 had not been able to reduce the TSS below the quality standard, while silica sand in both discharges were still in accordance with the quality standard. In the second stage of processing, Q1 MSL A-s had the best elimination capability, with the efficiencies of TDS, TSS, pH, and DO respectively being 18.13%, 79.68%, 2.60%, and 126.67%, while for Q2, they were 29.99%, 77.76%, 1.62%, and 95.80%. In the third stage, it was shown that MSL B-m was the most optimal reactor compared to all reactors that had their water qualities measured. For Q1 for MSL B-m, the parameters of TDS, TSS, pH, and DO were respectively 33.16%, 84.32%, 1.29%, and 126.67%, and for Q2 they were 30.80%, 80.54%, 1.50%, and 112.30%. In the third stage of processing, MSL A-m, MSL B-m, and MSL C-m that included the addition of soil mixtures and modifications of soil mixture blocks could increase the efficiency of each parameter and had a more stable quality of water outflow compared to standard MSL; this is because the incoming water flow was slower, which caused water contact with the processing media to be more optimal.